CHAPTER 3 - MUSEOLOGY AND COMMUNITY DEVELOPMENT IN THE XXI CENTURY (Cadernos de Sociomuseologia, 2009)
Since the late 60’s, many authors have worked to bring clarifications on the concepts of development applied to the museological field. Until the 90’s, professionals related to the new museology school of thought and MINOM’s philosophy virtually monopolized the efforts to conceptualize and explain community development. With the opening in the field to development issues, today it is possible to find references to community development theory and practice in other publications besides those originating from authors associated to the new museology. The same way as it happens with the broader field of development, it is not easy to define community development, once a number of variables come to shape ideas that only take concrete form in practice. That is to say, development is a truly ideological concept, being intimately related to the aspirations of each particular community. In this way, in order to understand the meaning of community development within the discourse of museology, one must take into account the assessment of theoretical variables (categorized here as key concepts, approaches and principles) under specific contexts and demands (described as development objectives). Before proceeding with their analysis, it seems necessary to present some connotations that accompany to the term “development”, not only within the museological field, but the field of development as a whole.